THEORETICAL INVESTIGATION OF INTERMEDIATE ELEMENT MOTION DYNAMICS OF ACOUSTIC OSCILLATING SYSTEM AT ITS VIBRO-IMPACT OPERATION MODE - M. G. Kiselev; A. A. Novikov (Наука и техника)
The results of theoretical investigation of the intermediate element motion dynamics at vibro- impact operation mode of acoustic oscillating system are given in the paper. The dependences reflecting the influence of acoustic and technological parameters on time and force characteristics of interaction between the intermediate element and the surface to be machined have been established and investigated.